Tailoring of the Local Environment of Active Ions in Rare-Earth- and Transition-Metal-Doped Optical Fibres, and Potential Applications - Dussardier, Bernard; Blanc, Wilfried; Peterka, Pavel (IntechOpen, 2012)
None